Islamic Education in the Modern Era: Analysis of Student Character and Their Role in Facing the Challenges of Industry 4.0 - Muzawir Munawarsyah (HEUTAGOGIA: Journal of Islamic Education, 2023)
This study explores the role of Islamic education in shaping student character in the context of the modern era, particularly amidst the challenges of Industry 4.0. Utilizing a qualitative methodology with a literature review approach, this research delves into historical perspectives on character, Islamic viewpoints on human nature, and contemporary learner characteristics, especially among Generation Z. Character in Islamic education is conceptualized as an amalgamation of innate traits and environmental influences, as reflected in Islamic teachings and the tripod theory of education. The study uncovers four primary streams of character formation - Fatalistic-Passive, Neutral-Passive, Positive-Active, and Dualistic-Active, aligning with Islamic teachings on children's innate purity and environmental impact. The analysis reveals that the rapid technological advancements characteristic of Industry 4.0 pose significant challenges to student character, leading to moral and ethical dilemmas. Islamic education emerges as a crucial tool for instilling values such as sincerity and respect for teachers while internalizing Islamic values within familial settings. The study emphasizes the need for an integrated educational approach that balances academic pursuits with character development, adapting Islamic education to modern challenges while retaining its core values. It contributes to the discourse on education, highlighting the role of religious teachings in contemporary educational practices. Recognizing its limitations, the study suggests further research into the application and long-term impact of character education across diverse educational settings.